Applying the Artistic Psychological Painting Course to Improve the Mental Health of Middle School Students - Xiaohang, Yu; Ladin, Che Aleha; Dayou, Deng; Lei, Nie; Zihao, Wang; Shuo, Wang; Xinghua, Li; Qinghong, Wu (American Journal of Education and Practice, 2023)
Purpose: This study aims to verify the significance of the Artistic Psychological Painting program for developing middle school students' psychological well-being through an educational program and a multi-factorial experimental design based on feedback from teachers and students. Methodology: This paper presents the format and content of the Artistic Psychological Painting program to test the program's effectiveness. The subjects were 12-15-year-old middle school students in the first and second grades of Southwest University South China Town Middle School (middle school) in Chongqing, China, and the Artistic Psychological Painting course they took at school. Findings: The study showed that the Artistic Psychological Painting program positively affected middle school students' emotional intelligence and self-identity. Accordingly, based on the initial definition and exploration of the connotation and extension of the Artistic Psychological Painting curriculum, we have communicated with school leaders, subject experts, in-service teachers, and students to propose the implementation of the "Artistic Psychological Painting". Recommendation: The program is designed to complement the psychological education curriculum in Chinese public schools and to provide a vision for school-based and community-based curricula.